An enzyme-triggered turn-on fluorescent probe based on carboxylate-induced detachment of a fluorescence quencher. Issue 42 (24th August 2020) - Oe, Masahiro; Miki, Koji; Ohe, Kouichi
Abstract : A new class of turn-on fluorescent probes for an enzyme was developed to increase the responsiveness to the enzyme without generating any by-products. Abstract : We developed a new class of turn-on fluorescent probes for an esterase. After the esterase-mediated hydrolysis produced carboxylate (as a fluorescence activator), the fluorescence intensity was markedly increased through the detachment of a quencher moiety from the quenched Cy5 fluorophore. Because the probes based on this new activator-induced quencher-detachment (AiQd) adopt a non-immolative linker between the cleavable site and the fluorophore, the rate of the enzymatic reaction is greatly improved, without the generation of any by-products.